2004
DOI: 10.1145/962081.962083
|View full text |Cite
|
Sign up to set email alerts
|

Managing conflict in software testing

Abstract: Conflict between software testers and developers is inevitable, but mindful managers minimize its effect on development projects through communication, mutual respect, even social interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 2 publications
1
60
0
Order By: Relevance
“…The role of the tester is to surface flaws and errors in developers' code (Cohen et al, 2004;Parkin, 2001). It is a type of systemic conflict that develops as a result of lateral working relationships (Pondy, 1967).…”
Section: Overview Of Interpersonal Conflict Antecedentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of the tester is to surface flaws and errors in developers' code (Cohen et al, 2004;Parkin, 2001). It is a type of systemic conflict that develops as a result of lateral working relationships (Pondy, 1967).…”
Section: Overview Of Interpersonal Conflict Antecedentsmentioning
confidence: 99%
“…Software developers and testers are very different from each other in terms of mindsets, goals, experiences, and perceptions of their relative importance (Cohen et al, 2004;Pettichord, 2000;Rothman, 2004). First, developers and testers often have different mindsets, as developers always think in terms of "building" something, whereas testers devise means of "breaking" what developers build.…”
Section: Overview Of Interpersonal Conflict Antecedentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather it is achieved implicitly through other agile practices, where multitasking and self-organisation are encouraged (Augustine 2005), roles and responsibilities are stated at a much higher level of granularity (Beck and Fowler 2001), short iterations mean that a developer need not be tied to a specific role for a long period of time Cockburn 2001;Schwaber and Beedle 2002), and pair programming and co-located teams allow easy observation between developers (Williams, Kessler et al 2000;Canfora, Cimitile et al 2005). Few researchers have examined the impact of creative abrasion and conflict in the ISD process (see Domino, Collins et al 2003 for a comprehensive literature review), despite the fact that Cohen et al (2003) found such conflict to be a frequent and significant occurrence on ISD projects. Newman and Robey (1992) state that the generation and resolution of conflict is of central theoretical interest to ISD researchers, yet there is "little empirical work relating to conflict handling styles and ISD" (Domino, Collins et al 2003).…”
Section: Creative Abrasionmentioning
confidence: 99%